Some Metallurgical and Engineering Aspects of the Rum Jungle Water Treatment Plant (The Australasian Institute of Mining and Metallurgy, 1984)
The reasons for including treatment of water in Whites and Intermediate open cuts in the overall rehabilitation strategy are given in the introduction. The target quality of the treated water also is discussed. Equipment selections are reviewed and reasons given as to why certain choices were made. The differences between this plant and an ore dressing mill are highlighted. An outline of the operating procedure is included along with a basic flowsheet. Cost estimates are briefly Discussed.